Developing Service Quality Index for Zakat Institutions - Wahab, Norazlina Abd.; Zainol, Zairy; Bakar, Mahyuddin Abu; Ibrahim, Ahmad Zubir; Minhaj, Norida (International Journal of Economics and Financial Issues, 2016)
The aim of this paper is to examine service quality of zakat institutions in Malaysia using an enhanced model appropriate for zakat institution. We use a new and enhanced model (combination of SERVQUAL and CARTER) to examine the extent of service quality of zakat institutions from the perspective of zakat stakeholders. Data were collected from 799 respondents including both zakat payers and zakat recipients. The paper utilizes the Structural Equation Modelling (SEM) in examining the extent of service quality given by zakat institution and further develops Service Quality Index (SQI) for both Zakat Payers and Zakat Recipients using a Customer Satisfaction Index. The results reveal that Responsiveness & Compliance was found to be the strongest indicator to influence satisfaction of the zakat payers while Reliability was found to be the strongest indicator to influence satisfaction of the zakat recipients. The SQI for zakat payers and zakat recipients of Malaysian zakat institutions are 76.3 and 76.4 respectively. This study is one of the first to examine the service quality of zakat institutions using an extended SERVQUAL and CARTER models with both zakat payers and zakat recipients as respondents. The model is not only relevant and applicable to Malaysia but also to other Muslim countries. Keywords: SERVQUAL, Service quality, Structural Equation Modelling (SEM), Zakat institution, Service Quality Index (SQI) JEL Classification: D63